2018
DOI: 10.1002/jum.14878
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Multiparametric Transrectal Ultrasound in Localized Prostate Cancer: A Comparative Study With Magnetic Resonance Imaging

Abstract: Objectives-The aim of this study was to compare the diagnostic performance of multiparametric transrectal ultrasound (TRUS), including grayscale imaging, color Doppler imaging, shear wave elastography, and contrast-enhanced ultrasound, to that of multiparametric magnetic resonance imaging (MRI), including T2-weighted, diffusion-weighted, and dynamic contrast-enhanced MRI, in the diagnosis of localized prostate cancer (PCa; lesions at stage T2 or lower).Methods-Seventy-eight patients were prospectively enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…In addition, Shoji et al [29] indicated that combining Prostate Imaging Reporting and Data System Scores (PI-RADS) with measurement of Young's modulus by three-dimensional SWE improved the diagnosis of clinically significant prostate cancer. Moreover, Zhang et al [41] also demonstrated that multiparametric TRUS including greyscale imaging, colour Doppler imaging, SWE and contrast-enhanced ultrasound yielded a higher SEN, negative predictive value and accuracy than did multiparametric MRI (97.4% versus 94.7%, 96.9% versus 92.3% and 87.2% versus 76.9%, respectively) for detecting localized PCa. Hence, based on the aforementioned findings, novel SWE-based techniques and systems with improved diagnostic accuracy have provided direction and evidence for the detection of PCa in the future.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Shoji et al [29] indicated that combining Prostate Imaging Reporting and Data System Scores (PI-RADS) with measurement of Young's modulus by three-dimensional SWE improved the diagnosis of clinically significant prostate cancer. Moreover, Zhang et al [41] also demonstrated that multiparametric TRUS including greyscale imaging, colour Doppler imaging, SWE and contrast-enhanced ultrasound yielded a higher SEN, negative predictive value and accuracy than did multiparametric MRI (97.4% versus 94.7%, 96.9% versus 92.3% and 87.2% versus 76.9%, respectively) for detecting localized PCa. Hence, based on the aforementioned findings, novel SWE-based techniques and systems with improved diagnostic accuracy have provided direction and evidence for the detection of PCa in the future.…”
Section: Discussionmentioning
confidence: 98%
“…[30] A comparative study by Zhang et al showed multiparametric TRUS (grayscale, color Doppler, shear wave elastography, and contrast enhanced ultrasound) had higher sensitivity, negative predictive value, and accuracy than multiparametric MRI (T2-weighted, diffusion-weighted, and dynamic contrast-enhanced MRI) in detecting localized PCa. [42] From evidences, TRUS has some advantages in detecting localized PCa from MRI with lower cost, real time, and higher availability.…”
Section: Discussionmentioning
confidence: 99%
“…The existing high level of evidence (Level I, Group 1) presenting the superiority of HDR brachytherapy boost complementary to external beam boost (11) raised the question if mpTRUS is eligible for intraprocedural definition of relevant dominant (high Gleason) subvolumes within the prostate. Controlled investigations stated the equality of mpTRUS with mpMRI (36,37); however, prospective randomized clinical trials are needed in the future.…”
Section: Discussionmentioning
confidence: 99%